Innate Immune Activity Correlates with CD4 T Cell-Associated HIV-1 DNA Decline during Latency-Reversing Treatment with Panobinostat - Olesen, Rikke (J Virol, 2015)
The pharmaceutical reactivation of dormant HIV-1 proviruses by histone deacetylase inhibitors (HDACi) represents a possible strategy to reduce the reservoir of HIV-1-infected cells in individuals treated with suppressive combination antiretroviral therapy (cART). However, the effects of such latency-reversing agents on the viral reservoir size are likely to be influenced by host immune responses. Here, we analyzed the immune factors associated with changes in proviral HIV-1 DNA levels during treatment with the potent HDACi panobinostat in a human clinical trial involving 15 cART-treated HIV-1-infected patients. We observed that the magnitude, breadth, and cytokine secretion profile of HIV-1-specific CD8 T cell responses were unrelated to changes in HIV-1 DNA levels in CD4 T cells during panobinostat treatment. In contrast, the proportions of CD3(−) CD56(+) total NK cells and CD16(+) CD56(dim) NK cells were inversely correlated with HIV-1 DNA levels throughout the study, and changes in HIV-1 DNA levels during panobinostat treatment were negatively associated with the corresponding changes in CD69(+) NK cells. Decreasing levels of HIV-1 DNA during latency-reversing treatment were also related to the proportions of plasmacytoid dendritic cells, to distinct expression patterns of interferon-stimulated genes, and to the expression of the IL28B CC genotype. Together, these data suggest that innate immune activity can critically modulate the effects of latency-reversing agents on the viral reservoir and may represent a target for future immunotherapeutic interventions in HIV-1 eradication studies. IMPORTANCE Currently available antiretroviral drugs are highly effective in suppressing HIV-1 replication, but the virus persists, despite treatment, in a latent form that does not actively express HIV-1 gene products. One approach to eliminate these cells, colloquially termed the “shock-and-kill” strategy, focuses on the use of latency-reversing agents that induce active viral gene expression in latently infected cells, followed by immune-mediated killing. Panobinostat, a histone deacetylase inhibitor, demonstrated potent activities in reversing HIV-1 latency in a recent pilot clinical trial and reduced HIV-1 DNA levels in a subset of patients. Interestingly, we found that innate immune factors, such as natural killer cells, plasmacytoid dendritic cells, and the expression patterns of interferon-stimulated genes, were most closely linked to a decline in the HIV-1 DNA level during treatment with panobinostat. These data suggest that innate immune activity may play an important role in reducing the residual reservoir of HIV-1-infected cells.